1988
DOI: 10.1111/j.1749-6632.1988.tb31912.x
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi Infections in Bavarian Forest Workers A Follow‐up Studya

Abstract: Erythema migrans borreliosis, the European equivalent of Lyme borreliosis, is endemic in Bavaria, situated in the Southeast of West Germany. It seems of particular interest to what extent a population group especially prone to tick bites by its occupation shows clinical and serological hints to an infection with Borrelia burgdorferi (Bb). In 1983 we examined 2 11 forest workers from different regions of Upper Bavaria clinically and tested their sera with regard to antibodies (Ab) against Bb by means of an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Indeed, this rate is decidedly better than the rates obtained with serologic testing in endemic populations, where seropositivity may approach 50% in asymptomatic subjects (35)(36)(37). It also compares favorably with the serologic false-positive rate of 15-30% that has been found in patients with certain rheumatic and infectious diseases (6,7).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, this rate is decidedly better than the rates obtained with serologic testing in endemic populations, where seropositivity may approach 50% in asymptomatic subjects (35)(36)(37). It also compares favorably with the serologic false-positive rate of 15-30% that has been found in patients with certain rheumatic and infectious diseases (6,7).…”
Section: Discussionmentioning
confidence: 97%
“…This patient probably had a reinfection, since erythema migrans occurs in general within three months (median period 2.5 weeks) after acquisition of Borrelia burgdorferi infection (18). We are aware of only three cases of Lyme borreliosis developing after established asymptomatic seropositivity (8,19,20). In two patients acrodermatitis chronica atrophicans (8,20) and in one patient radiculopathy and peripheral facial palsy developed two to four years after known seropositivity (21).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only three cases of Lyme borreliosis developing after established asymptomatic seropositivity (8,19,20). In two patients acrodermatitis chronica atrophicans (8,20) and in one patient radiculopathy and peripheral facial palsy developed two to four years after known seropositivity (21). These cases suggest long-lastzng asymptomatic persistent infection but reinfection cannot be excluded among these persons who were at a high risk for tick bites.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In 1988, we reported on a population of outdoor workers in New Jersey with an overall seroprevalence ofantibody toBorrelia buwgdorfer, the causative agent of Lyme disease, of 8.1% (56 of 689 workers had at least one positive serologic test). 4,5 Workers in this population who reported exposure to ticks on the job had a fivefold elevated risk of infection.…”
Section: Intodudionmentioning
confidence: 99%
“…Study variables included counties of work and residence; self-reported number of ticks noted on skin or clothing and tick bites in the past week, month, 3 …”
Section: Study Vanablesmentioning
confidence: 99%